(untitled) (Journal of Universal Science Research, 2023)
in order to develop the optimal sowing time, ensuring high and stable yields of soybeans of the “Nafis” variety in the Aral sea region,field experimental were carried out on the experiment plot of the Karakalpakistan scientific experimental station of the rechearch institute of grain leguminous crops. The experience in multi-factorial. Sowing was carried out in three sowing dates 1st,2nd,3rd ten daysof april. The results of the study showed that when cultivating soybeans of the Nafis variety in the aral sea region in order to oblain the highest grain yielts, sowing should be carried out in the first the day april.